PROFIL GURU, PEMAHAMAN KOOPERATIF NHT, DAN KEMAMPUAN BERPIKIR TINGKAT TINGGI DI SMP KABUPATEN MINAHASA UTARA - Kawuwung, Femmy (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2011)
The research aims to uncover a general profile of teachers, understanding cooperative NHT, and higher-order thinking skills in middle school biology teacher North Minahasa regency. Research methods: survey with a research instrument is a questionnaire consisting of questions developed is an open question and a combination of semi-closed and open questions that have been validated by experts of learning. The study population is a junior high science teacher in North Minahasa Biology. The questionnaire that was circulated questionnaires amounted to 40 and who entered and analyzed totaled 31. The study began in July and August 2010. The results are: Understanding the Biology of junior high science teacher in North Minahasa regency NHT 6.45% towards learning, and teachers' understanding of higher-order thinking skills 12.90%. Teachers' understanding of the NHT and the results of cooperative learning is still low.Keywords: Profile of Teachers, Science-Biology, NHT, High Thinking, Junior North Minahasa.